Single-species dinoflagellate cyst carbon isotope fractionation in core-Top sediments: environmental controls, CO2 dependency and proxy potential - Frieling, J; Van Roij, L; Kleij, I; Reichart, GJ; Sluijs, A (European Geosciences Union, 2023)
Sedimentary bulk organic matter and various molecular organic components exhibit strong CO2-dependent carbon isotope fractionation relative to dissolved inorganic carbon sources. This fractionation (p) has been employed as a proxy for paleo-pCO2. Yet, culture experiments indicate that CO2-dependent p is highly specific at genus and even species level, potentially hampering the use of bulk organic matter and non-species-specific organic compounds. In recent years, significant progress has been made towards a CO2 proxy using controlled growth experiments with dinoflagellate species, also showing highly species-specific p values. These values were, however, based on motile specimens, and it remains unknown whether these relations also hold for the organic-walled resting cysts (dinocysts) produced by these dinoflagellate species in their natural environment. We here analyze dinocysts isolated from core tops from the Atlantic Ocean and Mediterranean Sea, representing several species (Spiniferites elongatus, S. (cf.) ramosus, S. mirabilis, Operculodinium centrocarpum sensu Wall and Dale (1966) (hereafter referred to as O. centrocarpum) and Impagidinium aculeatum) using laser ablation-nano-combustion-gas-chromatography-isotope ratio mass spectrometry (LA/nC/GC-IRMS). We find that the dinocysts produced in the natural environment are all appreciably more 13C-depleted compared to the cultured motile dinoflagellate cells, implying higher overall p values, and, moreover, exhibit large isotope variability. Where several species could be analyzed from a single location, we often record significant differences in isotopic variance and offsets in mean 13C values between species, highlighting the importance of single-species carbon isotope analyses. The most geographically expanded dataset, based on O. centrocarpum, shows that p correlates significantly with various environmental parameters. Importantly, O. centrocarpum shows a CO2-dependent p above g1/4g€¯240g€¯μatm pCO2. Similar to other marine autotrophs, relative insensitivity at low pCO2 is in line with active carbon-concentrating mechanisms at low pCO2, although we here cannot fully exclude that we partly underestimated p sensitivity at low pCO2 values due to the relatively sparse sampling in that range. Finally, we use the relation between p and pCO2 in O. centrocarpum to propose a first pCO2 proxy based on a single dinocyst species.